FAKTOR YANG MEMENGARUHI MANAJEMEN LABA PERUSAHAAN NON KEUANGAN DI BURSA EFEK INDONESIA - Natasya Natasya; Umar Issa Zubaidi (E-Jurnal Akuntansi TSM, 2021)
The objective of this research is to obtain empirical evidence regarding the influence of firm size, firm financial leverage, firm age, firm’s audit quality, ownership concentration, managerial ownership, institutional ownership, foreign ownership, firm growth and return on asset as independent variables toward earnings management as dependent variable. This research period is three years from 2017-2019 using a population of all non financing companies listed in the Indonesia Stock Exchange and resulting 94 non financing companies that meet the research criteria using purposive sampling method. The result of this research shows that firm financial leverage, firm’s audit quality, firm growth and return on asset have influence on earnings management. However firm size, firm age, ownership concentration, managerial ownership, institutional ownership and foreign ownership have no influence on earnings management.